Research Ethics Committees and scientific publications (Orinoquia, 2013)
The United  Nations’  General Assembly  adopted and  proclaimed the Universal  Declaration of Human Rights once the  Second World  War and  its concomitant horrors  had  ended, stating  inarticle  27 that,  “Everyone  has the  right freely to participate in the  cultural  life of the  community, to enjoy  the  arts and  to share  in scientific advancement and  its benefits,”  and,  “Everyone  has the right to the protection of the moral and  material  interests resulting  from any scientific,  literary or artistic production of which  he is the  author.”The World  Medical Association’s  Declaration of Helsinki may be added to the  foregoing; it stated that  a research proposal’s pro- tocol  should  be submitted to an independent organ  for its, “consideration, comment, guidance and approval,” thereby giving birth to what  is known today  as a “Research Ethics Committee” (REC).